Fibrewise Multi-Perfect Topological Spaces - Y. Y. Yousif; M.H. Jaber; M. El Sayed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The essential objective of this paper is to introduce new notions of fibrewise topological spaces on D that are named to be upper perfect topological spaces, lower perfect topological spaces, multi-perfect topological spaces, fibrewise upper perfect topological spaces, and fibrewise lower perfect topological spaces. fibrewise multi-perfect topological spaces, filter base, contact point, rigid, multi-rigid, multi-rigid, fibrewise upper weakly closed, fibrewise lower weakly closed, fibrewise multi-weakly closed, set, almost upper perfect, almost lower perfect, almost multi-perfect, fibrewise almost upper perfect, fibrewise almost lower perfect, fibrewise almost multi-perfect, upper* continuous fibrewise upper∗ topological spaces respectively, lower* continuous fibrewise lower∗ topological spaces respectively, multi*-continuous fibrewise multi∗-topological spaces respectively multi-Te, locally In addition, we find and prove several propositions linked to these notions.